Inside Cover: Photocatalytic Water Oxidation by a Mixed‐Valent MnIII3MnIVO3 Manganese Oxo Core that Mimics the Natural Oxygen‐Evolving Center (Angew. Chem. Int. Ed. 42/2014). Issue 42 (14th August 2014) - Al‐Oweini, Rami; Sartorel, Andrea; Bassil, Bassem S.; Natali, Mirco; Berardi, Serena; Scandola, Franco; Kortz, Ulrich; Bonchio, Marcella
<x xml:space="preserve">Abstract</x> The engine of aerobic life on earth is a tetramanganese oxo cluster at the very heart of Photosystem II (PS II) in green plants, algae, and photosynthetic bacteria. In their Communication on page 11182 ff., F. Scandola, U. Kortz, M. Bonchio et al. have identified a unique hybrid set of ligands to provide the first functional analogue of the PS II oxygen‐evolving center that works in an artificial environment (Cover picture: Rami Al‐Oweini).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>